2016
DOI: 10.1016/j.marpolbul.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Marine sediment contamination and dynamics at the mouth of a contaminated torrent: The case of the Gromolo Torrent (Sestri Levante, north-western Italy)

Abstract: In this study we have examined the currents and hydrological characteristics of the water column off the mouth of the Gromolo Torrent (north-western Italy) in relation to the grain-size, mineralogical characteristics and metal distribution in the marine sediment sampled. Our purpose was to quantify and map the contamination that was carried out to sea from the abandoned Libiola Fe-Cu sulphide mine that has heavily impacted the torrent. Our results show high concentrations of Cu and Zn, and relatively high conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…Combining the results provided by all different analysis carried out in this study and according to results found by Capello et al (2016) and Consani et al (2019), a summary of the main characteristics of sediment and metal transport and diffusion on the continental shelf off the eastern part of the Gulf of Tigullio has been developed ( Fig. 8) and reported below:…”
Section: Marine Environment and Marine Sedimentsmentioning
confidence: 84%
See 4 more Smart Citations
“…Combining the results provided by all different analysis carried out in this study and according to results found by Capello et al (2016) and Consani et al (2019), a summary of the main characteristics of sediment and metal transport and diffusion on the continental shelf off the eastern part of the Gulf of Tigullio has been developed ( Fig. 8) and reported below:…”
Section: Marine Environment and Marine Sedimentsmentioning
confidence: 84%
“…Grain size analysis of sediments was conducted following methodology described in Capello et al ( 2016 ). Samples were wet sieved for grain size (Ø) > 63 mm (with 63, 125, 250, 500, 1000-μm steps for sand, and Ø > 2000 μm for gravel).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations